Ideas for mentorship in oncology for medical students and early career doctors: insights from a UK-wide oncology mentorship scheme - Joanna Kucharczak; Emma G. Khoury; Yarden Toiber Kent; Rahul Winayak; Simon Duke (BMC Medical Education)
Abstract Background Early mentorship in oncology increases interest in the field and benefits mentees and mentors both personally and professionally. The British Oncology Network for Undergraduate Societies (BONUS) Mentorship Scheme enables UK-wide pairing of students and early career doctors with trainee and consultant oncologists. Little is known about the content of the sessions. Here we describe the objectives, contents, and outcomes of the scheme. We provide ideas and aims that mentees and mentors can utilize for future mentoring. Methods A total of 101 mentors and 150 mentees were recruited from October 2022 to April 2023. Data were collected via pre-, mid-, and post-mentorship questionnaires. The questionnaires assessed the motivations, benefits, and improvements for the scheme with an overlying focus on the contents of the sessions. Qualitative data were analyzed via the framework method. Results The main expectations for mentees were to become involved in research and receive oncology career guidance. The mentors’ main motivation was to promote oncology as a career. The most desirable traits for a mentor reported by mentees were being approachable and proactive. The contents of the sessions consisted of discussions of the oncology career pathway, clinical shadowing, research projects and audits, discussions of oncology from clinical perspectives, signposting to career building opportunities, formal teaching, journal clubs and case discussions. Mentees enjoyed the scheme and found participation valuable. As a result, they became more interested in oncology. The benefits described by mentees included exposure to oncology and confirmation of oncology as the right career choice. Personal satisfaction was the most frequently reported benefit for mentors. Interestingly, we found a mismatch between mentees’ desire for research opportunities and the scheme’s ability to facilitate this. Conclusions Our study provides a comprehensive guide for mentorship ideas in undergraduate oncology. Our findings confirm the success of the BONUS Mentorship Scheme. We identify areas for future work, such as addressing the gap in cancer research opportunities for students and pre-specialty doctors.